Comparative Analysis of Real-time Traffic Information for Navigation and the Variable Speed Limit System. Issue 3 (2016) - Ackaah, Williams; Bogenberger, Klaus; Bertini, Robert L.; Huber, Gerhard
Abstract: Advanced traveler information system (ATIS) has been used and is viewed as an essential component for present-day traffic management. ATIS may provide information such as the traffic situation, incidents, and weather conditions which may adversely affect traffic. This information may be disseminated through media such as dynamic navigation devices and the variable speed limit (VSL) systems. The objective of this study was to examine whether there exist inconsistency in traffic information provided from different sources. The VSL and data for real-time traffic information (RTTI) for navigation systems were used as subjects for the study. The assessment was made by comparing the discretized space-time representation of ground truth (GT) speeds, reconstructed from inductive loop detector data, to the space-time traffic information displayed by the VSL or the navigation system. The discretization ensured that the method takes into consideration, limitations faced by the providers in broadcasting the information. The VSL system and data for navigation systems obtained from a private provider on the Autobahn A99, near Munich, were used as case study.